TextureMontage: Seamless Texturing of Arbitrary Surfaces From Multiple Images - Zhou, Kun; Wang, Xi; Tong, Yiying; Desbrun, Mathieu; Guo, Baining; Shum, Heung-Yeung (Association for Computing Machinery, Inc., 2005)
We propose a technique, called TextureMontage, to seamlessly map a patchwork of texture images onto an arbitrary 3D model. A texture atlas can be created through the specification of a set of correspondences between the model and any number of texture images. First, our technique automatically partitions the mesh and the images, driven solely by the choice of feature correspondences. Most charts will then be parameterized over their corresponding image planes through the minimization of a distortion metric based on both geometric distortion and texture mismatch across patch boundaries and images. Lastly, a surface texture inpainting technique is used to fill in the remaining charts of the surface with no corresponding texture patches. The resulting texture mapping satisfies the (sparse or dense) user-specified constraints while minimizing the distortion of the texture images and ensuring a smooth transition across the boundaries of different mesh patches.